(untitled) (Research, Society and Development, 2020)
The psychological terror caused by moral harassment is one of the psychological violence frequently used as a means of control and domination. The study aimed to analyze the characteristics of bullying in the work context in a medium-sized Brazilian municipality. It is an applied, descriptive and quantitative research, a survey. 190 workers participated. For data collection, a questionnaire developed and validated in Brazil was used. The main results indicate that there is no moral harassment in the work environment of most participants. When seeking to establish a statistical association between the categories, no result was evidently significant, since the averages of the responses, for the most part, were concentrated on the options never and rarely, which is stipulated as not suffering from bullying in the workplace. However, it is necessary to mention the small, but significant number of manifestations that show discrimination due to race, sex and sexual orientation, discrimination that can be expressed directly, causing suffering to the victim and constituting a crime.